2021
DOI: 10.1371/journal.ppat.1009987
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptional profiling of the early host response to infection by typhoidal and non-typhoidal Salmonella serovars in human intestinal organoids

Abstract: Salmonella enterica represents over 2500 serovars associated with a wide-ranging spectrum of disease; from self-limiting gastroenteritis to invasive infections caused by non-typhoidal serovars (NTS) and typhoidal serovars, respectively. Host factors strongly influence infection outcome as malnourished or immunocompromised individuals can develop invasive infections from NTS, however, comparative analyses of serovar-specific host responses have been constrained by reliance on limited model systems. Here we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…SE and STM share high levels of gene homology but accessory genes unique to SE contribute to its pathogenesis in a mouse model of infection (28)(29)(30). We also found that these serovars elicit unique responses by human intestinal epithelium (8). Consistent with this earlier finding, we observed clustering of SE-infected PMN-HIOs away from STMinfected PMN-HIOs via principal component analysis (PC2) (Fig.…”
Section: Pmn-hios Induce Unique Responses To Two Nontyphoidal Salmone...supporting
confidence: 87%
See 2 more Smart Citations
“…SE and STM share high levels of gene homology but accessory genes unique to SE contribute to its pathogenesis in a mouse model of infection (28)(29)(30). We also found that these serovars elicit unique responses by human intestinal epithelium (8). Consistent with this earlier finding, we observed clustering of SE-infected PMN-HIOs away from STMinfected PMN-HIOs via principal component analysis (PC2) (Fig.…”
Section: Pmn-hios Induce Unique Responses To Two Nontyphoidal Salmone...supporting
confidence: 87%
“…HIOs are derived from human pluripotent stem cells and self-organize to form a 3dimensional polarized epithelium with differentiated epithelial cells and an underlying mesenchyme (9). Bacteria, including Salmonella, are able to replicate and stimulate robust inflammatory responses in HIOs (6)(7)(8)(10)(11)(12). Although the HIO model and other tissue culture models have been invaluable in revealing human-specific responses to Salmonella infection (6)(7)(8)(13)(14)(15), key features missing from these models are known to shape the outcome of infection, including immune cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, secretory cell hyperplasia (goblet, paneth, and tuft cells), mucus, and AMP production such as Reg3γ and DEFA1 were induced in response to STm infection ( Lu et al, 2020 ). In addition, similar results indicating an inhibition of the cell turnover at the intestinal epithelium and intestinal epithelial secretion induced by STm infection in susceptible mice ( Santos et al, 2016 ) were also observed using human intestinal organoids microinjected with STm to model the bacterial infection at the apical side ( Abuaita et al, 2021 ). Interestingly, organoids from juvenile inflammatory bowel patient failed to control STm growth and highlight the role of IL22 and IL10RB gene in antimicrobial defense against STm ( Forbester et al, 2018 ).…”
Section: Relevance Of Intestinal Epithelial Organoids To Decipher ...supporting
confidence: 55%
“…Children under 5 years old bear the burden of the major disease, especially in low-income regions (Havelaar et al, 2015 ; GBD 2017 Non-Typhoidal Salmonella invasive disease collaborators , 2019 ; Gilchrist and MacLennan, 2019 ). NTS generally causes self-limiting diarrheal illness, but may typically lead to severe invasive NTS for children's lack of immunity (Abuaita et al, 2021 ; Rana et al, 2021 ). Infection with different NTS serovars can present various epidemiological and clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%